Does temporary agency work provide a stepping stone to regular employment? - Michael Kvasnicka (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
Based on administrative data from the federal employment office in Germany, we apply matching techniques to estimate the stepping-stone function of temporary agency work for the unemployed, i.e. its short-run and long-run effects on their future employment prospects. Our results show that unemployed workers who take up a job in the temporary work agency (TWA) industry are on average more likely than unemployed workers not joining TWA work to be in agency employment in the four year period these workers are tracked after entering TWA work. However, we find no discernable effects on the probabilities of being either in regular employment or registered unemployment. Our findings therefore do not lend support to the stepping-stone function of temporary agency work.
Keywords: C14; C41; J41; J64; 330; Temporary work agencies; stepping stone; evaluation; matching